A Prospective, Crossover Survey Study of Child- and Proxy-Reported Quality of Life According to Spinal Muscular Atrophy Type and Medical Interventions. (April 2020) - Weaver, Meaghann S.; Hanna, Rewais; Hetzel, Scott; Patterson, Karen; Yuroff, Alice; Sund, Sarah; Schultz, Meredith; Schroth, Mary; Halanski, Matthew A.
Background: Spinal muscular atrophy is an autosomal-recessive, progressive neuromuscular disease associated with extensive morbidity. Children with spinal muscular atrophy have potentially increased life spans due to improved nutrition, respiratory support, and novel pharmaceuticals. Objectives: To report on the quality of life and family experience for children with spinal muscular atrophy with attentiveness to patient- and proxy-concordance and to stratify quality of life reports by spinal muscular atrophy type and medical interventions. Methods: A prospective, crossover survey study inclusive of 58 children (26 spinal muscular atrophy type I, 23 type II, 9 type III) and their family caregivers at a free-standing Midwestern children's hospital. Twenty-eight families completed the 25-item PedsQL 3.0 Neuromuscular Module. Forty-four participants completed the 36-item PedsQL Family Impact Module and 47 completed the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) questionnaire. Results: The PedsQL Family Impact Module demonstrated significant differences between spinal muscular atrophy types I and II in functioning domains including physical, emotional, social, and family relations ( P < .03). Child self-report and proxy report surveys demonstrated significant differences between spinal muscular atrophy types in the communication domains ( P < .003). Children self-reported their quality of life higher than proxy report of child quality of life. Gastrostomy tube ( P = .001) and ventilation support ( P = .029) impacted proxy-reported quality of life perspectives, whereas nusinersen use did not. Spinal surgery was associated with improved parental quality of life and family impact ( P < .03). Conclusions: The measurement and monitoring of quality of life for children with spinal muscular atrophy and their families represents an implementable priority for care teams.